2022
DOI: 10.1186/s12981-022-00491-y
|View full text |Cite
|
Sign up to set email alerts
|

Stigma experienced by people living with HIV who are on methadone maintenance treatment and have symptoms of common mental disorders in Hanoi, Vietnam: a qualitative study

Abstract: Background Stigma around human immunodeficiency virus (HIV), injection drug use (IDU), and mental health disorders can be co-occurring and have different impacts on the well-being of people living with HIV (PWH) who use drugs and have mental health disorders. This stigma can come from society, health professionals, and internalized stigma. A person who has more than one health condition can experience overlapping health-related stigma and levels of stigma which can prevent them from receiving n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This underscores the detrimental effect of stigma on the mental health of individuals with MS, leading them to adopt emotion-focused strategies that adversely impact their adjustment and quality of life (31). Corroborating these results, Tran et al (32) found that HIV patients with greater internalized stigma tended to use more emotion-focused strategies. Similarly, Holubova et al (33) demonstrated a direct and significant link between the use of emotion-focused coping strategies and increased internalized stigma in schizophrenia patients.…”
Section: Discussionmentioning
confidence: 92%
“…This underscores the detrimental effect of stigma on the mental health of individuals with MS, leading them to adopt emotion-focused strategies that adversely impact their adjustment and quality of life (31). Corroborating these results, Tran et al (32) found that HIV patients with greater internalized stigma tended to use more emotion-focused strategies. Similarly, Holubova et al (33) demonstrated a direct and significant link between the use of emotion-focused coping strategies and increased internalized stigma in schizophrenia patients.…”
Section: Discussionmentioning
confidence: 92%